2020
DOI: 10.1111/jfbc.13467
|View full text |Cite
|
Sign up to set email alerts
|

Identification of octopus peptide and its promotion of β‐casein synthesis in a mouse mammary epithelial cell line

Abstract: Octopus protein hydrolysate has been reported to increase milk yield and milk protein production. In this paper, the utilization and underlying mechanisms of bioactive peptide fractions from octopus protein hydrolysate on β-casein expression in mouse mammary epithelial cells (HC11) were investigated. Fraction OPH3-1 significantly stimulated cell proliferation and β-casein synthesis in HC11 cells, which was purified by ultra-filtration and gel-filtration chromatography. The MWs of the peptides from OPH3-1 range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…STAT5 binds to the gene promoter region of milk proteins by recognizing its specific binding motifs . Prolactin and glucocorticoid activate the proximal promoter of CSN 2 and induce β-casein expression in mouse mammary epithelial cells. , Essential amino acid and prolactin increase CSN 2 expression and β-casein synthesis by activating STAT5 signaling in BMEC. , Furthermore, STAT5a binds with the CSN 2 promoter and activates β-casein transcription in immortalized GMEC . Consistent with these data, luciferase assays have shown that STAT5 also could activate CSN 2 promoter activity in GMEC.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…STAT5 binds to the gene promoter region of milk proteins by recognizing its specific binding motifs . Prolactin and glucocorticoid activate the proximal promoter of CSN 2 and induce β-casein expression in mouse mammary epithelial cells. , Essential amino acid and prolactin increase CSN 2 expression and β-casein synthesis by activating STAT5 signaling in BMEC. , Furthermore, STAT5a binds with the CSN 2 promoter and activates β-casein transcription in immortalized GMEC . Consistent with these data, luciferase assays have shown that STAT5 also could activate CSN 2 promoter activity in GMEC.…”
Section: Discussionmentioning
confidence: 58%
“…42 Prolactin and glucocorticoid activate the proximal promoter of CSN2 and induce β-casein expression in mouse mammary epithelial cells. 43,44 Essential amino acid and prolactin increase CSN2 expression and β-casein synthesis by activating STAT5 signaling in BMEC. 45,46 Furthermore, STAT5a binds with the CSN2 promoter and activates β-casein transcription in immortalized GMEC.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Studies also showed that after stimulation of BMECs with tripeptides and lactogenic hormones, the abundance of PepT1 and PepT2 can be increased, thereby promoting milk fat synthesis [85,86]. In addition, it has been shown that OPH3-1, a fraction of the octopus protein hydrolysis product bioactive peptide, promotes mammary epithelial cell proliferation and casein synthesis in mice [87].…”
Section: Peptidesmentioning
confidence: 99%